Kewenangan Pengelolaan Wisata Alam Sebagai Destinasi Wisata Daerah di Wilayah Kecamatan Padarincang Kabupaten Serang Berdasarkan Peraturan Daerah Nomor 8 Tahun 2014 tentang Rencana Induk Pembangunan Kepariwisataan Kabupaten Serang Tahun 2014-2025 - iqbal iqbal Iqbal; Mohammad Fasyehhudin (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
Padarincang sub-district has tourism potential because it has good natural resources, including many mountains and very large rivers so that there are many natural attractions. The existence of this potential provides opportunities for tourism management to local governments and the community to increase natural tourism in Padarinenag sub-district so that it becomes a leading tourist destination in Serang Regency and has an impact on the welfare of the community. This potential must be followed by better management, therefore this study will discuss about how to manage natural tourism as a regional tourist destination in the Padarincang sub-district based on Serang district regulation number 8 of 2014 ?. What are the obstacles for the attacking district government in exercising its authority over the management of natural tourism as a regional tourist destination in the Padarincang sub-district area? The research method used is juridical empirical, namely research that sees law as a rule in society to be obeyed, with descriptive analysis specifications that discuss the management of natural tourism as a regional destination in the Padarincang sub-district which is sourced from primary data through field research and primary legal materials, namely legislation. -laws, books, journals of legal science, as well as other library materials that are analyzed juridically analytic. The results of this study, that the Serang Regency Tourism Office is tasked with managing the tourism of the serang regency area with the aim of increasing the prosperityand walfare of the serang regency area. The management of natural tourism carried out by the Serang Regency Tourism Office on natural tourism in the Padarincang District area is already good and is in accordance with the duties and functions based on Regional Regulation Number 8 of 2014 concerning Serang Regency tourism development master plan in 2014-2025. However, in carrying out its management there are a few obtstacles and this is an obstacle to natural tourism in order to become a superior and enchanting tourism destination. Thus the Tourism Office must improve its performance in managing tourist destinations on the chat, especially eliminhating these obstacles.